PENGEMBANGAN LEMBAR AKTIVITAS SISWA (LAS) MENGGUNAKAN PENDEKATAN DIFFERENTIATED INSTRUCTION UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK - Ade Evi Fatimah; Azrina Purba (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The purpose of this study is to produce quality student activity sheets. To achieve this, this research uses development research. The development model used in this study is a 4-D development model consisting of the Define, Design, Development and Disseminate stages. The subject of this research is the tenth grade students of SMK 1 Percut Sei Tuan Deli Serdang Regency and the object of this research is the mathematics student activity sheet of trigonometry material using the Differentiated Instruction (DI) approach. Developed in this study is the student activity sheet (LAS). The results of the study show that: (1) the level of mastery learning in classical is 83.33%; (2) the level of student activity during the learning process takes place on the ideal time tolerance criteria; (3) the level of the teacher's ability to manage learning is good, because the average has reached the minimum criteria; (4) student responses to the components of the device and the learning process are positive; (5) Mathematical problem solving abilities of students have increased with an average value of 1.457 at pretest and 3.103 in postes with an average increase (N Gain) included in the medium category with an average of 0.521. The researcher suggested that the Differentiated Instruction approach be an alternative for teachers to improve students' mathematical problem solving abilities.Keywords: Student Activity Sheet, Differentiated Instruction Approach, mathematical problem solving ability